Pemanfaatan Zakat Mualaf Berbasis Inovasi Tepung Sagu Sebagai Rotipenakuk di Desa Kubalahin Kabupaten Buru - Wael, Abdi (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Lolongguba is the second largest sago producing sub-district in Buru Regency after Teluk Kayeli Sub-district, which has a sago area with a production of 16 tons of sago flour per month. Lolongguba District, which is the center for processing and producing sago, is Kubalahin Village, the majority of whose population are Muslim converts who have converted to Islam since 2009 and earn their living as gardeners and sago farmers. The partner's problem is the lack of knowledge about innovations in processing sago flour into a consumer product with various flavors and not having adequate equipment and equipment to support the implementation of activities, as well as processing techniques, entrepreneurship methods and marketing systems that can increase economic value. The aim of community service activities is to introduce the community to innovation skills in entrepreneurship which are oriented towards development, empowerment and improving the economy, through the use of Mualaf Zakat towards this to achieve output targets with the implementation target of empowering business groups, developing business and entrepreneurship skills besides that. to increase economic value through income from sales of processed Sago Flour products. From this Penakuk Roti product innovation, attractive labels will be made on the product packaging and promotions will be carried out by placing banner advertisements in front of partners' houses and also business groups